Early Identification of Learning and Developmental Disorders in School-Age Children - Hasan Phudinawala; Irfana Batatawala; Ruhisha Samnani (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The aim of developing an online quiz assessment tool is to identify learning disabilities like ‘Dyslexia’, ‘Dyscalculia’, ‘ADHD’ and ‘Anxiety’ as early as possible in children for better educational outcomes. This study applied modern web technologies, such as HTML, CSS, JavaScript, PHP, and FLASK to come up with an easy interface that combines the extensive questionnaire with analytical algorithms. This tool also collects user data as they use it and hence gives information and feedback to a user as well as other stakeholders instantly. By means of user testing, the interface was characterized as easily applicable which contributed to the increase of the attention to the educational needs of the target audience. The main conclusions are that the tool promotes the detection of learning disorders in children as early as possible and encourages minimizing delays in treatment. The presented project is also focused on the application of technologies in the management of development difficulties as well as principles of design that are aimed at making the assessment tools more useful.